The implementation of problem-based learning to improve manipulative fundamental movement outcomes - Akbar, M. Khoirul; Mujtahidin, Afiq Hakim; Ridwan, Mochamad (CV. Nusantara Sporta, 2024)
This inquiry about points to uncover the essential manipulative development abilities, particularly tossing and catching the ball, in review IVB understudies at UPT SDN 168 Gresik through applying the problem-based learning (PBL) show. This thinks about included 18 understudies, comprising 8 guys and 10 females, who took part in two cycles of fundamental manipulative development learning. The instrument utilized in this think-about was a perception sheet that centred on manipulative development assignments (tossing and catching). Information was analyzed utilizing qualitative and quantitative clear strategies. Within the beginning cycle, the comes about appeared an increment in tossing capacity by 27% and catching by 23%, with a completion rate of 50% for catching and 61% for tossing. Within the moment cycle, there was an advance increment, specifically 33% in tossing capacity and 13% in catching capacity, with completion coming to 83% for tossing and 78% for catching. Based on these comes about, it can be concluded that the problem-based learning (PBL) demonstrated is successfully connected to manipulative development learning in physical instruction, sports and wellbeing subjects.